Civilization - Gill, Michael; Clark, Lord (London : BBC Enterprises, 1993)
Lord Clark, writer, scholar and possibly the most advocate of the traditions of Western art and culture, seek out the answers to these age old questions. Travelling across 80,000 miles and 16 centuries, he presents his own epic forour times: the story of Western man's most glorious achievements in architecture, art, philosophy, literature and music
Copy available in DVD format
Title from data sheet
Keywords: Civilization, Western; Civilization, Modern -- 20th century